Analisis Akuntansi Aset Tetap Berdasarkan Pernyataan Standar Akuntansi Pemerintah (PSAP) No. 7 Tahun 2010 Tentang Aset Tetap pada Kecamatan Lubuk Sikarah Kota Solok - Ramadhani, Zahra; Mustika, Rasyidah; Rosita, Irda (Universitas Batanghari Jambi, 2025)
This study aims to analyze fixed asset accounting based on Government Accounting Standards Statement (PSAP) No. 7 of 2010 concerning fixed assets in Lubuk Sikarah District, Solok City. The method used is a qualitative approach, with data collection techniques including interviews, observation, and documentation. Data analysis was carried out using indicators based on PSAP No. 7 of 2010, namely classification, recognition, initial measurement and assessment, subsequent expenditures, subsequent measurement, termination and disposal, and disclosure. The results of the study indicate that the implementation of fixed asset accounting in Lubuk Sikarah District is largely in accordance with PSAP No. 7 of 2010, although there are still shortcomings in the aspects of termination, disposal, and presentation and disclosure. The main obstacles lie in the lack of documentation and difficulties in tracing the acquisition value due to recording that has not been well integrated.